SISTEM PENDUKUNG KEPUTUSAN PENGAJUAN PENERIMA BANTUAN WARGA MISKIN KOTA TULUNGAGUNG BERBASIS WEB MENGGUNAKAN METODE SAW - Mufidatul Islamiyah (Universitas Narotama, 2020)
The process of determining underprivileged people in Tulungagung are not running efficiently if there is no basic method in the calculation. This study focuses on calculating the determination of underprivileged people using decision support systems based on variables and weight values that are determined on the basis of existing system requirements to obtain the best alternative value (Vi). In this study used Simple Additive Weighting method, also called weighted addition. The basic concept of this method is to find a weighted sum of performance ratings on each alternative on all criteria. First, the existing system is improved by adding criteria and sub criteria. The new dataset consists of 9 criteria with 4 sub- criteria in each criterion. The data used for testing are data from Banyuurip village residents, Kalidawir Subdistrict, Tulungagung. Data of underprivileged people is implemented as alternative data which has 9 criteria (Ci) which have been weighted used to calculate match rating values and make decision matrices to calculate normalized matrix R. The final step is ranking, which is the multiplication of normalized matrix R with weight vector so that the biggest value is obtained and chosen as the best alternative (Ai) as the solution. In the trials that have been carried out on 110 population data as an alternative has been obtained ranking of the 20 largest taken and then compared with manual calculations with the results 20 of these data are appropriate. This means this system is 100% valid.